Análise de resultados da aplicação da teoria das restrições na confecção de peças de vestuário - Silva, Raul Nunes da (2023)
In the current scenario, in which fashion is more and more diversified and with relatively transitory trends, these issues intensify the need for designers to adapt to market requirements, since not keeping up with this quickness will cause them to lose space in the market, opening opportunities for new competitors. These changes have a direct impact in the production system of companies, therefore, it is necessary to act firmly in the improvement of productive management in clothing. That said, this work has as main goal to evaluate the operational productivity through the implementation of the theory of restrictions in the manufacturing cells, through a Monthly monitoring and evaluation of the obtained results. To achieve this goal, a study case was carried out, with research methodology of an applied nature, with a quantitative approach and explanatory nature. Concerning to methodological procedures, interviews, available document analysis and on- site observations were included for better understanding. To support this study, topics such as Production Management, Theory of Restrictions, Capacity and Control Planning, and Production Balancing were explored. From the implementation and monitoring, it was possible to identify the factors that influenced the use of production units, and therefore make the necessary comparisons to understand how the Theory of Restrictions impacts the result of a production system. In addition, to reinforce some questions and justifications, a questionnaire with the leadership of the productive area (clothing) was applied. However, it was observed that the correct application and constant monitoring of the TOC methodology is capable of increasing productivity gains, because the result of the small production unit (PUP 25) studied had na increase of 4.5%, in relation to the period where there was no structured implementation, as well as proper monitoring.